Mechanisms of transcranial direct current stimulation (tDCS) for pain in patients with fibromyalgia syndrome - Wang, Shan; Du, Shu-Hao; Wang, Xue-Qiang; Lu, Jun-Yan (Frontiers in Molecular Neuroscience, 2024)
Fibromyalgia syndrome (FMS) is a recurrent pain condition that can be challenging to treat. Transcranial direct current stimulation (tDCS) has become a promising noninvasive therapeutic option in alleviating FMS pain, but the mechanisms underlying its effectiveness are not yet fully understood. In this article, we discuss the most current research investigating the analgesic effects of tDCS on FMS and discuss the potential mechanisms. TDCS may exert its analgesic effects by influencing neuronal activity in the brain, altering cortical excitability, changing regional cerebral blood flow, modulating neurotransmission and neuroinflammation, and inducing neuroplasticity. Overall, evidence points to tDCS as a potentially safe and efficient pain relief choice for FMS by multiple underlying mechanisms. This article provides a thorough overview of our ongoing knowledge regarding the mechanisms underlying tDCS and emphasizes the possibility of further studies to improve the clinical utility of tDCS as a pain management tool.